PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN KEPUASAN KERJA TERHADAP KINERJA KEPALA SEKOLAH MENENGAH ATAS DI JAKARTA TIMUR - Sutji Harijanto (Jurnal Manajemen Pendidikan, 2010)
This survey focuses on the effects of organizational culture, leadership style and job satisfaction on senior high school principals' performance in East Jakarta. Sixty schools were selected randomly as a unit of analysis and data were analyzed by path analysis. Findings of the research indicated direct effects of: 1) Organizational culture and leadership style on job satisfaction, and 2) Organizational culture, leadership style, and job satisfaction on the principal’s performance. The results also showed indirect effect of organizational culture and leadership style on the principal’s performance through job satisfaction. In addition, job satisfaction was the most dominant variable that effected senior high school principal’s performance.